2018
DOI: 10.1074/jbc.ra118.005606
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural characterization of the chikungunya virus translational recoding signals

Abstract: Climate change and human globalization have spurred the rapid spread of mosquito-borne diseases to naïve populations. One such emerging virus of public health concern is chikungunya virus (CHIKV), a member of the Togaviridae family, genus Alphavirus. CHIKV pathogenesis is predominately characterized by acute febrile symptoms and severe arthralgia, which can persist in the host long after viral clearance. CHIKV has also been implicated in cases of acute encephalomyelitis, and its vertical transmission has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 67 publications
(77 reference statements)
3
27
0
Order By: Relevance
“…The portion of the transcript containing the EE and LL mutations is over 100 nucleotides upstream from the ribosomal slip site, and should therefore not perturb the stimulatory RNA structures that are currently believed to modulate -1PRF. 2,22,23 These mutations instead alter the portion of the nascent chain that falls just outside of the ribosomal exit tunnel during -1PRF, which suggests the nascent chain itself may stimulate frameshifting. Though it has yet to be implicated in ribosomal frameshifting, the cotranslational membrane integration and/ or folding of the nascent chain is known to generate tension on the ribosome.…”
Section: Impact Of Nascent Chain Forces On Ribosomal Frameshiftingmentioning
confidence: 99%
See 1 more Smart Citation
“…The portion of the transcript containing the EE and LL mutations is over 100 nucleotides upstream from the ribosomal slip site, and should therefore not perturb the stimulatory RNA structures that are currently believed to modulate -1PRF. 2,22,23 These mutations instead alter the portion of the nascent chain that falls just outside of the ribosomal exit tunnel during -1PRF, which suggests the nascent chain itself may stimulate frameshifting. Though it has yet to be implicated in ribosomal frameshifting, the cotranslational membrane integration and/ or folding of the nascent chain is known to generate tension on the ribosome.…”
Section: Impact Of Nascent Chain Forces On Ribosomal Frameshiftingmentioning
confidence: 99%
“…Current evidence suggests -1PRF is stimulated by a canonical poly-U slip site and a downstream RNA hairpin. 23 However, an effort to map the stimulatory RNA structures within alphavirus polyproteins revealed that deletions within the predicted hairpin region are capable of reducing the efficiency of -1PRF, but appear to be insufficient to knock out frameshifting completely. 22 This observation suggests there may be multiple regulatory mechanisms that mediate -1PRF within the alphavirus structural polyprotein.…”
Section: Introductionmentioning
confidence: 99%
“…The portion of the transcript containing the EE and LL mutations is over 100 nucleotides upstream from the ribosomal slip site, and should therefore not perturb the stimulatory RNA structures that are currently believed to modulate -1PRF. 1,16,17 These mutations instead alter the portion of the nascent chain that falls just outside of the ribosomal exit tunnel during -1PRF, which suggests the nascent chain itself may stimulate frameshifting. Though it has yet to be implicated in ribosomal frameshifting, the cotranslational membrane integration and/ or folding of the nascent chain is known to generate tension on the ribosome.…”
Section: Impact Of Nascent Chain Forces On Ribosomal Frameshiftingmentioning
confidence: 99%
“…The frameshift reporter (mKate) was fused 100 nucleotides downstream from the slip site in order to avoid disrupting the stimulatory RNA hairpin downstream from the slip sites. 16,17 This design avoids recently described artefacts associated with dual-luciferase PRF reporters in two ways. 33 First, the transcripts of our fluorescent expression reporter (eGFP) does not contain any cryptic splice sites.…”
Section: Plasmid Preparation and Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation